Individual and combined effects of land use and weeds on Cry1Ab/c protein expression and yield of transgenic cry1Ab/c rice. Issue 1 (31st December 2022) - Fu, Jianmei; Liu, Biao
ABSTRACT: Considering the anticipated commercial exploitation of insect-resistant transgenic rice and that the planting area of cultivated rice overlaps with wild rice, simulating an escape of transgenic rice from farmlands and exploring its fitness after entering semi-natural or natural ecosystems through uncontrolled seed dispersal or gene flow are critical to understand the resulting potential long-term environmental risks. The expression of foreign Cry1Ab/c protein and vegetative and reproductive fitness of insect-resistant transgenic rice Huahui1 (HH1) and its parental-line Minghui63 (MH63) were studied under four treatments combining land use and weed competition: farmland and uncultivated land under weed control (F-NW and U-NW, respectively), and farmland and uncultivated land without weed control (F-W and U-W, respectively). The expression of Cry1Ab/c was significantly lower in U-NW, F-W, and U-W than that in the control treatment, F-NW. Except for plant height, key vegetative (tiller number and biomass) and reproductive (grain number and grain weight per plant) growth indices of transgenic HH1 were significantly lower than those of the parental-line MH63 in F-NW and U-NW, indicating a significant fitness cost. In F-W and U-W, vegetative growth indices (plant height, tiller number, and biomass) were similar in HH1 and MH63; however, key reproductive indices including seed-set rate were significantly higher in HH1 than in MH63, indicating significant fitness benefits. Although these results support large-scale cultivation of insect-resistant transgenic rice in China, the ecological risk involved is high in farmland or uncultivated land without weed control (F-W and U-W).